Hoodwinked an economic hit man reveals why the global economy imploded - and how to fix it - Perkins, John. (New York Crown Business, 2011)
John Perkins has seen the signs of today's economic meltdown before. The subprime mortgage fiascos, the banking industry collapse, the rising tide of unemployment, the shuttering of small businesses across the landscape are all too familiar symptoms of a far greater disease. In his former life as an economic hit man, he was on the front lines both as an observer and a perpetrator of events, once confined only to the third world, that have now sent the United States?and in fact the entire planet?spiraling toward disaster.
Includes bibliographical references and index.
Keywords: Global Financial Crisis, 2008-2009; Economic history -- 21st century; Finance -- Government policy